A Study of Quality of Journals with TCI Database Criteria Case Study of Walailak University Academic Journals - Sirirak, Kosin; Kongsri, Yuwatida (Dhammathas Academic Journal, 2019)
This research aims to encourage and reinforce the quality development of journals with Thai-Journal Citation Index (TCI) database criteria: Case study of Walailak University academic journals. The target group were selected from 3 journal’s editors are Walailak Abode of Culture Journal, Journal of Learning Innovations Walailak University, and Walailak Journal of Social Sciences. Data was analyzed using TCI database criteria, analyzing the potential for the journals, and focus group discussion. The results are classified into (1) group of journals for quality development with TCI database criteria are Walailak Abode of Culture Journal, Journal of Learning Innovations Walailak University, and (2) group of journals for the highest quality development in TCI database (Tier 1) is Walailak Journal of Social Sciences. Three journals of Walailak University have been developed to meet the quality standards of the TCI database all of these 10 criteria. Moreover, it has also developed an online journal system (E-Journal) to make journals more effective, low cost for publication, universality, full journal content available online, increase referral opportunities, and can be accessed from anywhere. The results of these analyses showed that journals were indexed by TCI database are Walailak Abode of Culture Journal, Journal of Learning Innovations Walailak University, and Walailak Journal of Social Sciences. In addition, the editorial staffs of the journal are knowledgeable and able implement the standards of the TCI database.